A comparative study of the anti-microbial properties of commercially-available toothpastes in the Philippines - Cabrera, Maria Lourdes B.
Five toothpastes namely Close-UP, Gold Colgate, Lacalut aktive, Maxam and Pepsodent were tested for their in-vitro anti-microbial effect against Beta-hemolytic Streptococcus, Enterococci, Staphylococcus aureus and Candida albicans. Enterococci, Staphylococcus aureus and Candida albicans. The anti-microbial effects of these toothpastes were determined and compared based on their amounts of .5 grams and 1 gram with time exposures of 3 minutes and 5 minutes. Results obtained from this study revealed that Close-Up, Lacalut aktive, Maxam and Pepsodent possess antimicrobial properties at varying degree against all the selected microorganisms. Gold Colgate has no absolute effect on Staph. aureus but has anti-microbial effects than using .5 grams of toothpaste. Also, 5-minute exposures of the microorganisms to the toothpastes are more efficient in reducing microbial growth than the 3-minute exposure time. Lacalut aktive possesses better anti-microbial properties over the other toothpastes studied.